Phytochemical profiles of edible flowers of medicinal plants of Dendrobium officinale and Dendrobium devonianum. Issue 12 (4th October 2021) - Zhao, Ming; Fan, Jiakun; Liu, Qianting; Luo, Hui; Tang, Qingyan; Li, Chongping; Zhao, Jurun; Zhang, Xinfeng
Abstract: The discovery of new edible flowers that are nontoxic, innocuous flowers having human health benefits, surveys of their phytochemicals and utilization are of great scientific and commercial interest. Dendrobium officinale and Dendrobium devonianum are precious Traditional Chinese Medicine. During the massive commercial cultivation, a lot of flowers were produced and certified as edible flowers, and the phytochemical profiles and bioactivities warrant evaluate. The present study aimed to investigate the phytochemicals and antioxidative activities in flowers of D. officinale (DOF) and D. devonianum (DDF). In total, 474 metabolites were identified using a widely targeted metabonomics method, 16 amino acids and 6 flavonoids were measured using high‐performance liquid chromatography (HPLC), and 8 fatty acids were detected using gas chromatography–mass spectrometry (GC‐MS). Both flowers contained various amino acids, including 7 essential amino acids, diverse flavonoids, especially quercetin, kaempferol and their derivatives, and high levels of methyl linoleate and methyl linolenate. The relative levels of quercetin, kaempferol and their glycosides were higher in DDF than in DOF, whereas the relative levels of several flavonoids C‐glycosides were high in DOF. Ethanol extracts of both DOF and DDF showed antioxidative capacities including the scavenging of 1, 1‐diphenyl‐2‐picrylhydrazyl and hydroxyl radicals. Both edible flowers contained flavonoids, amino acids, and fatty acids and have antioxidative activities, which should be explored for use in functional foods and pharmaceuticals. Abstract : Dendrobium officinale and Dendrobium devonianum are precious Traditional Chinese Medicines. During the massive commercial cultivation, a lot of flowers were produced and certified as edible flowers, and the phytochemical profiles and bioactivities warrant evaluate. The present study aimed to investigate the phytochemicals and antioxidative activities in flowers of D. officinale (DOF) and D. devonianum (DDF).Both edible flowers contained flavonoids, amino acids and fatty acids, and have antioxidative activities, which should be explored for use in functional foods and pharmaceuticals.